2021
DOI: 10.3126/njb.v9i1.38645
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Pattern of Staphylococcus aureus Isolated from Pus/Wound Swab from Children Attending International Friendship Children's Hospital

Abstract: A wound gets infected when the organism gets invaded through the breached skin, proliferated and production of various enzymes, toxins, etc. In order to treat the wound infection, antibiotic susceptibility pattern of organism should be determined before the prescription of the medicine. The present study was conducted from September 2017 to March 2018 with an aim to determine antibiotic susceptibility pattern of Staphylococcus aureus identified from the pus/wound swab among the patients visiting the Internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
(54 reference statements)
3
4
0
Order By: Relevance
“…S. aureus is 100% susceptible to teicoplanin and doxycycline in our study. This is similar to the study of Maharjan et al [23] . In a study of Deka et al [24] , S. aureus were 100% susceptible to clindamycin, which is in contrary to the findings of our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…S. aureus is 100% susceptible to teicoplanin and doxycycline in our study. This is similar to the study of Maharjan et al [23] . In a study of Deka et al [24] , S. aureus were 100% susceptible to clindamycin, which is in contrary to the findings of our study.…”
Section: Discussionsupporting
confidence: 93%
“…S. aureus is 100% susceptible to teicoplanin and doxycycline in our study. This is similar to the study of Maharjan et al 23 …”
Section: Discussionsupporting
confidence: 93%
“…In this study, the distribution of S. aureus among gender was found to be higher in female than male patients (56.02% vs 43.98%). The finding resembled with the research conducted by Maharjan et al 4 and Pradhan et al 13 The result obtained from the present study was contrast to previous studies 5,14,15 which showed the incidence of S. aureus was much higher in males than in females. The reason could be partly due to the infection rate between genders depending on geography and year of study.…”
Section: Discussionsupporting
confidence: 86%
“…2 S. aureus was isolated quite commonly in hospitals and medical facilities, causing a serious impact on human health, despite efforts to get rid of bacteria. [3][4][5] Currently, there have been many studies showing that S. aureus is increasingly resistant to antibiotics and spread of multidrug resistant (MDR). Notably, methicillinresistant S. aureus (MRSA) is a global health problem, causing many difficulties in treatment and prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation